Integration Theory Of Planned Behavioral (TPB) in Disclosing Corporate Social Responsibility (CSR) Through The Triple Bottom Line - Nurul Fuada (www.amertainstitute.com, 2024)
The theory of planned behavior (TPB) is one of the most effective theories in predicting human behavior when linked to corporate social responsibility research in determining corporate sustainability. This article aims to examine attitudes, subjective norms, perceived behavioral control and representation in disclosing corporate social responsibility through the triple bottom line. This article uses the Systematic Literature Review (SLR) method with 34 articles as references in the research. The results of this article show that there is integration between the Theory of planned behavior (TPB) in disclosing corporate social responsibility through the triple bottom line (social, environmental and economic aspects). This article contributes academically to the preparation of a new conceptual framework model related to the integration of the Theory of planned behavior (TPB) in disclosing corporate social responsibility through the triple bottom line.